2023
DOI: 10.3390/antiox12061277
|View full text |Cite
|
Sign up to set email alerts
|

Lady’s Bedstraw as a Powerful Antioxidant for Attenuation of Doxorubicin-Induced Cardiotoxicity

Abstract: This study aimed to examine the effects of a 14-day treatment with lady’s bedstraw methanol extract on doxorubicin-induced cardiotoxicity through functional, biochemical and histological examinations. We used 24 male Wistar albino rats divided into the following groups: control (CTRL), doxorubicin (DOX), and DOX + GVE (Galium verum extract). GVE was administered orally at a dose of 50 mg/kg per day for 14 days, while a single dose of doxorubicin was injected into the DOX groups. After accomplishing treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…This study also showed cardiac dysfunction in Langendorff-perfused rat hearts isolated from DOXadministered rats. LVDP, EDP, LV + dP/dt, and LV -dP/dt as markers for LV contractile markers were impaired in the DOX group, indicating contractile dysfunction, in line with previous results 22 . The study identi ed several mechanisms underlying cardiac dysfunction triggered by DOX, including heightened generation of reactive oxygen species (ROS) resulting in oxidative stress damage, disturbed calcium ion (Ca 2+ ) homeostasis, and compromised expression of genes associated with the apoptosis and necrosis of cardiomyocytes 34 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also showed cardiac dysfunction in Langendorff-perfused rat hearts isolated from DOXadministered rats. LVDP, EDP, LV + dP/dt, and LV -dP/dt as markers for LV contractile markers were impaired in the DOX group, indicating contractile dysfunction, in line with previous results 22 . The study identi ed several mechanisms underlying cardiac dysfunction triggered by DOX, including heightened generation of reactive oxygen species (ROS) resulting in oxidative stress damage, disturbed calcium ion (Ca 2+ ) homeostasis, and compromised expression of genes associated with the apoptosis and necrosis of cardiomyocytes 34 .…”
Section: Discussionsupporting
confidence: 92%
“…In extending our exploration to rat models, the in uence of CAR on DIC was evaluated by performing functional, biochemical, and histological examinations. The induction of cardiomyopathy in rats was achieved by administering a single cumulative intraperitoneal dose of DOX at 15 mg/kg to create a DOXinduced acute cardiotoxicity model, a well-established method documented in previous studies 22,23 . In addition, the risk of cardiotoxicity with DOX becomes signi cant when cumulative doses exceed 200 mg/m 2 , equivalent to 5 mg/kg in humans 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The DOX has been shown to cause an imbalance of redox status and attenuation of the antioxidants that led to the oxidization of macromolecules, leading to liver injuries [10,[39][40][41]. Allied with previous results, the study showed a significant increase in the MDA levels with a reduction in GSH levels herein in DOX-injected rats; this could be assigned to the impaired hepatic tissue under the damaging effects of DOX.…”
Section: Discussionsupporting
confidence: 73%
“…The pathological changes of DOX-induced heart injury are complex, such as oxidative stress, inflammatory response, endoplasmic reticulum stress, DNA damage, apoptosis, autophagy, mitochondrial dysfunction, disturbed calcium homeostasis, and fibrosis 4 9 . Among them, oxidative stress and apoptosis have been demonstrated to be important factors for the development of DOX-induced heart injury 10 , 11 . Therefore, alleviating oxidative stress and apoptosis may be a promising strategy for the treatment of DOX-induced heart injury.…”
Section: Introductionmentioning
confidence: 99%